The study of homology between tumor progression genes and members of retroviridae as a tool to predict target-directed therapy failure - Fernandes, Janaina (Frontiers in Pharmacology, 2015)
Oncogenes are the primary candidates for target-directed therapy, given that they are involved directly in the progression and resistance of tumors. However, the appearance of point mutations can hinder the treatment of patients with these new molecules, raising costs and the need to development new analogs that target the novel mutations. Based on an analysis of homologies, the present study discusses the possibility of predicting the failure of a protein as a pharmacological target, due to its similarities with retrovirus sequences, which have extremely high mutation rates. This analysis was based on the molecular evidence available in the literature, and widely-used and well-established PSI-BLAST, with two iterations and maximum of 500 aligned sequences. The possibility of predicting which newly-discovered genes involved in tumor progression would likely result in the failure of targeted therapy, using free, simple and automated bioinformatics tools, could provide substantial savings in the time and financial resources needed for long-term drug development.